Penerapan Metode Diskusi Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Fikih di Kelas XI Madrasah Aliyah Miftahussalam Medan - Dwi Hanny Putri Ezari; Nurhalima Tambunan; Kamil Kamil (Islamic Education, 2026)
This study aims to examine the implementation of the discussion method in improving students’ critical thinking skills in Fiqh learning and to identify factors influencing its implementation in Grade XI at Madrasah Aliyah Miftahussalam Medan. The study employed a descriptive qualitative approach involving the principal, Fiqh teachers, and Grade XI students as participants. Data were collected through observation, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that the discussion method contributes positively to students’ critical thinking development, reflected in increased learning participation, greater confidence in expressing opinions, improved ability to analyze Fiqh-related issues, and stronger logical argument construction. However, several challenges were identified, including differences in students’ academic abilities, low self-confidence, and limited instructional time. This study emphasizes that structured discussion and effective teacher facilitation are essential to support active learning and optimize students’ critical thinking development.